An Analysis of the Role of Fiscal Policy in Controlling CO2 Emissions in the Industrial Sector in Indonesia - Viola Novaryca; Nayla Desviona; Lizabeth Sari Dewi; Asramid Yasin (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
Climate change and the growing dependence on fossil fuels have intensified the challenge of aligning Indonesia’s industrial development with its emission reduction commitments. This study analyzes the role of fiscal policy in controlling CO₂ emissions in Indonesia’s industrial sector during the period 2010–2023, with a particular focus on three fiscal instruments: carbon taxation, fossil fuel subsidies, and government expenditure on the energy and environmental sectors. Using a descriptive-analytical approach based on secondary time-series data from national greenhouse gas inventories, state budget documents, government reports, and international energy publications, this study compares the dynamics of industrial CO₂ emissions with the development of fiscal policy instruments. The findings show that industrial CO₂ emissions generally increased throughout the observation period, with a temporary decline during the COVID-19 pandemic and a sharp rebound in 2022–2023. This increase was closely associated with the expansion of energy-intensive industries and the continued reliance on coal-based energy, particularly in manufacturing and mineral processing activities. Fiscal policy has not yet provided a coherent emission-control signal. Carbon tax implementation remained limited and has not directly affected the manufacturing sector, while fossil fuel subsidies continued to create price distortions that weakened incentives for energy efficiency and renewable energy adoption. At the same time, government spending on environmental and renewable energy programs remained relatively small compared with the scale of fossil fuel subsidies. This study concludes that Indonesia’s fiscal policy still operates in two opposing directions: supporting emission reduction through carbon pricing and green expenditure, while simultaneously sustaining carbon-intensive industrial activity through energy subsidies. Strengthening fiscal coherence is therefore essential to align industrial growth with Indonesia’s low-carbon transition agenda.